#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge - Hänel, Hilkje C (Philosophy & Social Criticism, 2022)
Two decades ago, Tarana Burke started using the phrase ‘me too’ to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article’s concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of ‘proper’ sexual violence and accounts that are not ‘proper’ experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.
Keywords: #metoo; approches et analyses; cours; cycles supérieurs; discipline; fem9000; justice sociale; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; violences sexuelles

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

La puissance féministe - Gago, Verónica (Éditions de la rue Dorion, 2021)
L’Amérique du Sud est un des coeurs battants du féminisme contemporain. Des millions de femmes y prennent la rue contre les féminicides, les violences qui frappent les minorités de race et de genre, les lois qui répriment l’avortement et le développement néo-extractiviste. Figure majeure du féminisme latino-américain, Verónica Gago réinscrit ces bouleversements dans l’émergence d’une internationale féministe et propose, avec La puissance féministe, un antidote à tous les discours de culpabilité et de victimisation. En se réappropriant l’arme classique de la grève, en construisant un féminisme populaire, radical et inclusif, les mouvements sud-américains ont initié une véritable révolution. C’est à partir de l’expérience de ces luttes que Gago reconceptualise la question du travail domestique et de la reproduction sociale, expose les limites du populisme de gauche et dialogue avec Spinoza, Marx, Luxemburg ou Federici. Parce qu’il unit la verve politique du manifeste aux ambitions conceptuelles de la théorie, La puissance féministe est un livre majeur pour saisir la portée internationale du féminisme aujourd’hui.
Keywords: 2000 à aujourd'hui; amérique latine; amériques; approches et analyses; care; cours; cycles supérieurs; fem7000; histoire et politique; justice sociale; militance; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences

Applied epistemology - Lackey, Jennifer (Oxford University Press, 2021)
Leading philosophers bring the tools of contemporary epistemology to bear on some of the most pressing social and political questions facing us as agents in the world today. This volume explores a diverse range of topics as they relate to epistemology under broad themes including injustice, race, feminism, sexual consent, and the internet.
Le texte d' Emmalon Davis, “A Tale of Two Injustices: Epistemic Injustice in Philosophy” a été donné au cours FEM9000.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; histoire et politique; injustice; justice sociale; philosophie; sciences humaines; thématiques; violences; épistémologie; éthique

Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Un féminisme décolonial - Vergès, Françoise (La fabrique, 2019)
Dans le débat public, être décolonial est une infamie. Dans les universités, dans les partis de gauche et d'extrême gauche, les syndicats, les associations féministes, partout on traque une "pensée décoloniale" infiltrée et funeste pour le vivre-ensemble. Dans ce livre, Françoise Vergès élucide l'objet du scandale. Le féminisme décolonial révèle les impensés de la bonne conscience blanche ; il se situe du point de vue des femmes racisées : celles qui, travailleuses domestiques, nettoient le monde ; il dénonce un capitalisme foncièrement racial et patriarcal. Ces pages incisives proposent un autre récit du féminisme et posent toutes les questions qui fâchent : quelles alliances avec les femmes blanches? Quelle solidarité avec les hommes racisés? Quelles sont les premières vies menacées par le capitalisme racial? Pourquoi les néofascismes s'attaquent-ils aux femmes racisées? Ce livre est une invitation à renouer avec la puissance utopique du féminisme, c'est-à-dire avec un imaginaire à même de porter une transformation radicale de la société.
https://www-cairn-info.proxy.bibliotheques.uqam.ca/un-feminisme-decolonial–9782358721745.htm
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; OFDIG; anticapitalisme; approches et analyses; com5170; cours; cycles supérieurs; europe; fem1000; fem7000; france; féminisme décolonial; har4600; incontournable; justice sociale; lit4700; pol4212; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; théories féministes

Le développement social et le travail social collectif : incantation magique ou orientation stratégique ? - Avenel, Cyprien (VST - Vie sociale et traitements, 2017)
Keywords: approches et analyses; cours; cycles supérieurs; discipline; europe; fem7000; france; justice sociale; régions géographiques; sciences humaines; travail social

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Les femmes face au pouvoir. Une réflexion sur l’empoderamiento - León, Magdalena (Cahiers du Genre, 2017)
L’usage du terme "empoderamiento" par le féminisme est étroitement lié à l’importance que l’idée de pouvoir a acquise dans les mouvements sociaux comme dans les théories en sciences sociales. Dans les analyses réalisées par Gramsci, Foucault et Paulo Freire, le pouvoir se définit comme un rapport social historiquement et culturellement déterminé. Même si ces auteurs ne font aucune référence directe au pouvoir inscrit dans les rapports de genre et n’utilisent pas le mot empoderamiento , ou ses équivalents, leurs analyses ont inspiré les réflexions que va développer le Mouvement des femmes. À partir de ce qu’on a appelé la ‘deuxième vague’ du fémi-nisme des années 1970, des groupes apparaissent qui commencent à faire usage du terme empoderamiento ou empowerment et à débattre de sa signification. Son utilisation par le Mouvement des femmes se présente comme une stratégie pour impulser le changement dans la vie quotidienne des femmes et la mise en œuvre d’un processus de transformation dans les structures sociales.
Cet article est tiré de l'introduction du livre : León Magdalena (ed) (1997). Poder y empoderamiento de las mujeres. Bogotá, Tercer Mundo.
Keywords: 1900-1999; 1970-1979; amérique latine; amériques; approches et analyses; cours; cycles supérieurs; discipline; empowerment; fem7000; histoire et politique; justice sociale; mouvements féministes; périodes historiques; rapports de domination; rapports de pouvoir; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; thématiques

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Le travail social entre émancipation et normalisation : une voie étroite pour les approches féministes - Modak, Marianne; Martin, Hélène; Keller, Véréna (Nouvelles Questions Feministes, 2013)
Édito
https://www.jstor.org/stable/24586389
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; féminisme matérialiste; histoire et politique; justice sociale; point de vue situé; pratiques féministes; rapports sociaux de sexe; sciences humaines; thématiques; théorie critique; travail social; émancipation

Logiques de genre dans l'enseignement associatif : carrières et pratiques militantes dans des associations revendicatives, 2013 - Rétif, Sophie (Dalloz, 2013)
Thèse pour le doctorat en science politique de l’Institut d’Etudes Politiques de Paris présentée et soutenue sous le titre Genre et engagement associatif. Carrières et pratiques militantes dans six associations françaises et portugaises. Tout espace social où s’organisent des rapports de genre apporte à leur structuration sa contribution propre. Cela veut dire qu’il faut ici prendre au sérieux les idéologies, les croyances comme affectant les anticipations et comportements ouverts aux femmes et hommes au sein des associations. (…) Ici encore, avec ce confort de lecture qui consiste à offrir des analyses stimulantes et bien construites sans les hérisser d’une envahissante signalétique théorique, Sophie Rétif met en oeuvre les fondamentaux d’une analyse de genre intelligente.
Keywords: activisme; approches et analyses; cours; cycles supérieurs; discipline; europe; fem7000; france; idéologie; inégalités; justice sociale; militance; mouvements sociaux; organisations féministes; portugal; rapports de domination; rapports sociaux de sexe; recherche comparative; recherche en milieux de pratique; reproduction sociale; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; travail; étude de cas; étude qualitative

Relational Knowing and Epistemic Injustice: Toward a Theory of Willful Hermeneutical Ignorance - Pohlhaus, Gaile (Hypatia, 2012)
I distinguish between two senses in which feminists have argued that the knower is social: 1. situated or socially positioned and 2. interdependent. I argue that these two aspects of the knower work in cooperation with each other in a way that can produce willful hermeneutical ignorance, a type of epistemic injustice absent from Miranda Fricker's Epistemic Injustice. Analyzing the limitations of Fricker's analysis of the trial of Tom Robinson in Harper Lee's To Kill a Mockingbird with attention to the way in which situatedness and interdependence work in tandem, I develop an understanding of willful hermeneutical ignorance, which occurs when dominantly situated knowers refuse to acknowledge epistemic tools developed from the experienced world of those situated marginally. Such refusals allow dominantly situated knowers to misunderstand, misinterpret, and/or ignore whole parts of the world.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; histoire et politique; ignorance herméneutique; injustices herméneutiques; injustices épistémiques; justice sociale; patriarcat; philosophie; privilèges; racisme; sciences humaines; systèmes d'oppressions; thématiques; éthique

The Relevance of Credibility Excess in a Proportional View of Epistemic Injustice: Differential Epistemic Authority and the Social Imaginary - Medina, José (Social Epistemology, 2011)
This paper defends a contextualist approach to epistemic injustice according to which instances of such injustice should be looked at as temporally extended phenomena (having developmental and historical trajectories) and socially extended phenomena (being rooted in patterns of social relations). Within this contextualist framework, credibility excesses appear as a form of undeserved epistemic privilege that is crucially relevant for matters of testimonial justice. While drawing on Miranda Fricker's proportional view of epistemic justice, I take issue with its lack of attention to the role that credibility excesses play in testimonial injustices. I depart from Fricker's view of the relation between credibility excesses and credibility deficits, and I offer an alternative account of the contributions that undeserved epistemic privileges make to epistemic injustices. Then, through the detailed analysis of To kill a mockingbird, I elucidate the crucial role played by the social imaginary in creating and sustaining epistemic injustices, developing an analysis of the kind of social blindness produced by an oppressive social imaginary that establishes unjust patterns of credibility excesses and deficits.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; histoire et politique; injustices épistémiques; inégalités; justice sociale; philosophie; privilèges; privilèges de crédibilité; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; éthique

Les transformations de la relation d'aide dans l'intervention sociale - Astier, Isabelle (Informations sociales, 2009)
Avec les dispositifs d’insertion, nous sommes entrés dans l’ère du travail avec autrui. Les professionnels et bénévoles de l’intervention sociale pensent désormais la relation d’aide à partir de la posture de l’accompagnement. Le souci premier des politiques sociales est de travailler la relation de l’individu défaillant avec la société et de le doter des capacités nécessaires pour infléchir le cours de sa vie, surmonter une rupture biographique, anticiper une difficulté. Que ce soit les politiques d’insertion, de proximité, d’accompagnement, de prise en charge de la dépendance ou de la souffrance psychique et sociale, toutes sont traversées par une logique de reconnaissance des formes de réalisation de soi.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; europe; fem7000; intervention sociale; justice sociale; régions géographiques; sciences humaines; travail social

Mobilisations improbables et apprentissage d'un répertoire syndical - Collovald, Annie; Mathieu, Lilian (Politix, 2009)
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; cycles supérieurs; europe; fem7000; france; justice sociale; mobilisation; périodes historiques; régions géographiques; syndicalisme; thématiques; travail

Epistemic injustice: Power and the ethics of knowing - Fricker, Miranda (Oxford University Press, 2007)
In this exploration of new territory between ethics and epistemology, Miranda Fricker argues that there is a distinctively epistemic type of injustice, in which someone is wronged specifically in their capacity as a knower. Justice is one of the oldest and most central themes in philosophy, but in order to reveal the ethical dimension of our epistemic practices the focus must shift to injustice. Fricker adjusts the philosophical lens so that we see through to the negative space that is epistemic injustice. The book explores two different types of epistemic injustice, each driven by a form of prejudice, and from this exploration comes a positive account of two corrective ethical-intellectual virtues. The characterization of these phenomena casts light on many issues, such as social power, prejudice, virtue, and the genealogy of knowledge, and it proposes a virtue epistemological account of testimony. In this ground-breaking book, the entanglements of reason and social power are traced in a new way, to reveal the different forms of epistemic injustice and their place in the broad pattern of social injustice."–Book cover. Justice is one of the oldest and most central themes of philosophy, but sometimes we would do well to focus instead on injustice. This book argues that there is a distinctively epistemic genus of injustice, in which someone is wronged specifically in their capacity as a knower
https://oxford-universitypressscholarship-com.proxy.bibliotheques.uqam.ca/view/10.1093/acprof:oso/9780198237907.001.0001/acprof-9780198237907
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; justice sociale; phi4336; premier cycle; ressource en ligne; sciences humaines; thématiques; épistémologie

Conceituando Empoderamento na Perspectiva Feminista - Sardenberg, Cecília M B (2006)
Transcription d’une communication au séminaire International : « Trilhas do empoderamento de mulheres », Salvador da Bahia, 5-10 juin 2006.
Keywords: amérique latine; amériques; anthropologie; approches et analyses; brésil; cours; cycles supérieurs; discipline; empowerment; fem7000; inégalités; justice sociale; militance; mouvements sociaux; patriarcat; pratiques féministes; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; épistémologie

Pour dépasser l’analyse structurale de l’engagement militant - Mac Adam, Doug (Le désengagement militant, 2005)
4e de couverture : L'un des traits permanents des organisations politiques, qu'elles soient partisanes, syndicales ou associatives, est bien le turn over et par conséquent la défection. À ce constat s'en ajoute un autre : la littérature sur le militantisme politique s'est essentiellement posé la question du recrutement et de l'enrôlement de nouveaux militants, mais elle demeure peu prolixe sur le maintien des engagements et, ce qui revient au même, le désengagement. Dans cet ouvrage qui rassemble parmi les meilleurs spécialistes contemporains du militantisme politique, ce sont les processus qui conduisent les individus à se désengager qui sont au centre de l'analyse, contribuant ainsi à poser d'une manière renouvelée la question du militantisme comme activité sociale spécifique, avec ses phases de recrutement et ses moments de déprise. Derrière la grande variété des groupements étudiés, du Parti communiste aux mouvements de lutte contre le sida, en passant par les centrales syndicales et le mouvement féministe américain, c'est bien une série de mécanismes propres à la sortie de rôle qui, dévoilés ici, offrent, sinon un modèle général du désengagement, du moins des pistes pour comprendre les logiques individuelles et collectives de la défection et un moyen nouveau de compréhension du destin des organisations.
Disponible en ligne : https://serval.unil.ch/resource/serval:BIB_38127.P001/REF.pdf
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; justice sociale; militance; ressource en ligne; sciences humaines; sociologie; thématiques

La "conscientisation" dans le militantisme des années 1970 - Mathieu, Lilian (Discours savants, discours militants: mélange des genres, 2002)
"OGM, nucléaire, principe de précaution, comité de sages, experts… autant de figures ou de domaines pour lesquels science et politique sont étroitement imbriquées. Le recours dans le débat public à la science et à l'expertise semble constituer une ressource politique susceptible de convaincre efficacement. Les auteurs montrent la diversité des usages militants des discours savants et saisissent les conditions de " passage " des discours d'un univers à l'autre."– Site de l'éditeur.
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; justice sociale; militance; pédagogie; périodes historiques; ressource en ligne; science politique; science politique et droit; thématiques

Questionnements féministes et méthodologie de la recherche - Ollivier, Michèle; Tremblay, Manon (L'Harmattan, 2000)
La recherche féministe repose-t-elle sur une éthique de la recherche qui lui est propre, Est-elle mieux servi par les méthodes qualitatives que quantitatives ? Comment arrive-t-elle à concilier engagement politique et effort d'élaboration d'un discours vrai sur le monde ? Cet ouvrage présente quelques éléments essentiels de la réflexion féministe actuelle sur la méthodologie de la recherche en sciences humaines et sociales.
Keywords: approches et analyses; canada; cours; cycles supérieurs; discipline; discours; fem1000; fem7000; har4600; justice sociale; méthodologie; point de vue situé; premier cycle; pédagogie; sciences humaines; sciences sociales; thématiques; épistémologie